Passively Q-switched pulses generation from Erbium-Doped fiber laser using Lutetium Oxide as saturable absorber - Mohamed, Nasser; Hamida, Belal Ahmed; Eltaif, Tawfig; Jafry, Afiq; Sulaiman, Harun (2021)
In this paper, a configuration of a passively Q-switched Erbium-doped fiber laser (EDFL) using a Lutetium Oxide (Lu2O3) thin film as a saturable absorber (SA) is experimentally implemented to generate high pulse energy with a high signal to noise ratio. A stable Q-switched pulse train is initiated at the input pump power of 30.442mW, and maximum pulse energy of 16.11 nJ is obtained at an output power of 0.97 mW, which confirms the stability of the pulses. It was possible to increase the repetition rate of the Q-switched laser from 31.25 to 60.2 kHz as the pump power was raised from 30.442 mW to 71.652 mW. Moreover, the pulse width decreased from 11.4 µs to 4.27 µs and 66.4 dB of the received signal-to-noise ratio at the radio frequency spectrum was achieved.